A(5a+c)-2a(c-4a)=

Simple and best practice solution for A(5a+c)-2a(c-4a)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for A(5a+c)-2a(c-4a)= equation:


Simplifying
A(5a + c) + -2a(c + -4a) = 0
(5a * A + c * A) + -2a(c + -4a) = 0
(5aA + cA) + -2a(c + -4a) = 0

Reorder the terms:
5aA + cA + -2a(-4a + c) = 0
5aA + cA + (-4a * -2a + c * -2a) = 0

Reorder the terms:
5aA + cA + (-2ac + 8a2) = 0
5aA + cA + (-2ac + 8a2) = 0

Reorder the terms:
5aA + -2ac + 8a2 + cA = 0

Solving
5aA + -2ac + 8a2 + cA = 0

Solving for variable 'a'.

The solution to this equation could not be determined.

See similar equations:

| 4x+y+2=43 | | 3/4(-x+4)=-3+3x | | 10-8/9x=-9 | | 3/10+[-1/5]= | | 2t^2-7t+5=0 | | 3/4(x-4)=-3+3x | | 10y-15=25 | | 3/4(x+4)=-3+3x | | 2*18(x+3)=34 | | 3x-6x+5-7x+8= | | Cw+w-cm-m=0 | | r-43=-33 | | v^2-15v+54=0 | | -2p+5p-9=3(p-4)-5 | | (3z+1)(4z+1)(6z+1)(12z+1)=2 | | 7x-4=3x+1+9x-5 | | -4-7x=2x+15 | | 4r-9=55 | | 4x+14(-14)-3+(-14)= | | 16+8x=24+6x | | -4(-x+4)=-4x+16 | | 16-4x= | | 7x-4=-3x+1+9x-5 | | x(30-x)=176 | | -94=-17+-7m | | -4(x-4)=-4x+16 | | 7n=50+35 | | 5x-10=14+7x | | 0.2x+0.15(50)=25.5 | | 5=RAIZ(2)+6RAIZ(3)+RAIZ(2)-2RAIZ(3) | | (-9r^3+2r-1)-(-5r^2+6x^2)= | | y=x(x^2-3) |

Equations solver categories